An Intelligent IEQ Monitoring and Feedback System: Development and Applications. (November 2022) - Geng, Yang; Zhang, Zhongchen; Yu, Juan; Chen, Hongzhong; Zhou, Hao; Lin, Borong; Zhuang, Weimin
Abstract: Indoor environmental quality (IEQ) significantly affects human health and wellbeing. Therefore, continuous IEQ monitoring and feedback is of great concern in both the industrial and academic communities. However, most existing studies only focus on developing sensors that cost-effectively promote IEQ measurement while ignoring interactions between the human side and IEQ monitoring. In this study, an intelligent IEQ monitoring and feedback system—the Intelligent Built Enviroment (IBEM)—is developed. Firstly, the IBEM hardware instrument integrates air temperature, relative humidity, CO2, particulate matter with an aerodynamic diameter no greater than 2.5 μm (PM2.5 ), and illuminance sensors within a small device. The accuracy of this integrated device was tested through a co-location experiment with reference sensors; the device exhibited a strong correlation with the reference sensors, with a slight deviation ( R 2 > 0.97 and slopes between 1.01 and 1.05). Secondly, a wireless data transmission module, a cloud storage module, and graphical user interfaces (i.e., a web platform and mobile interface) were built to establish a pathway for dataflow and interactive feedback with the occupants of the indoor environments. Thus, the IEQ parameters can be continuously monitored with a high spatiotemporal resolution, interactive feedback can be induced, and synchronous data collection on occupant satisfaction and objective environmental parameters can be realized. IBEM has been widely applied in 131 buildings in 18 cities/areas in China, with 1188 sample locations. Among these applications, we report on the targeted IEQ diagnoses of two individual buildings and the exploration of relationships between subjective and objective IEQ data in detail here. This work demonstrates the great value of IBEM in both industrial and academic research.